2015
DOI: 10.1167/iovs.15-16494
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Predictors for Good Versus Poor Visual Outcomes in the Treatment of Neovascular Age-Related Macular Degeneration With Intravitreal Anti-VEGF Therapy

Abstract: Eyes with neovascular AMD managed with a TER of anti-VEGF therapy having type 1 neovascularization at baseline were more likely to maintain good vision over 4 years, whereas clopidogrel use predicted poor vision at 2 years. Vision at 3 months was the best predictor for favorable long-term vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 36 publications
3
23
1
1
Order By: Relevance
“…One study found that type 1 CNV was associated with better long‐term vision compared to types 2 and 3 (Chae et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that type 1 CNV was associated with better long‐term vision compared to types 2 and 3 (Chae et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the vitreomacular interface, it was found that the presence of VMA was associated with relatively poor visual outcomes, with patients having a complete PVD showing higher visual gains (Nomura et al 2014;Uney et al 2014). One study found that type 1 CNV was associated with better long-term vision compared to types 2 and 3 (Chae et al 2015).…”
Section: Prognostic Indicators From Retrospective Trialsmentioning
confidence: 99%
“…Analyses of trial data suggested that continuous monthly treatment (vs pro re nata ) was associated with a higher risk of incident atrophy and faster atrophy progression over 1–2 years 58 . This effect varies with the neovascularization subtype 812 and may depend on the specific anti-VEGF agent used 8 . In contrast, when followed 5 years or more, vision loss may progress more slowly in eyes receiving a continuous vs pro re nata anti-VEGF regimen 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Current methods used to identify "good" and "poor" responders include stratifying disease status by markers of structure or function using tools such as optical coherence tomography (OCT) 6 , fluorescein angiography for lesion type 7 , and visual acuity tests 8 . Some imaging biomarkers such as the presence of intra retina fluid [9][10][11] and clinical signs such as poor starting vision 12,13 are associated with long-term poor prognosis, but these biomarkers do not precisely predict response to anti-VEGF treatment.…”
mentioning
confidence: 99%